Impact of loop diuretic dosage in a population of patients with acute heart failure: a retrospective analysis - Meani, P.; Pagnoni, M.; Mondellini, G. M.; Fiorenza, S.; Brunner-La Rocca, H. P. (Frontiers in Cardiovascular Medicine, 2023)
Background: Loop diuretics are essential for managing congestion in acute heart failure (AHF) patients, but concerns exist about their dosing and administration. This study aims to explore the relationship between aggressive diuretic treatment and clinical outcomes in AHF patients.Methods: We randomly selected 370 AHF patients from admissions at Maastricht University Medical Center between January 2011 and March 2017. Patients were divided into four quartiles based on diuretic doses administrated during index hospitalization. The primary endpoint was a composite of cardiovascular (CV) rehospitalization or death at 1 year.Results: 42.4% of patients experimented the primary outcome The composite endpoint rates were 35.4%, 41.6%, 38.5%, and 54.9%, respectively, from lowest to highest dose quartiles (p = 0.033). In univariate analysis, the outcome was significantly lower in the first three quartiles as compared to the fourth quartile.One-year CV mortality was 9.1%, 10.1%, 20.9% and 27.2%, respectively (p = 0.002). After adjusting for confounders, the association between loop diuretic dosage disappeared for both the primary outcome and one-year CV mortality. Most secondary outcomes (clinical and laboratory impacts) and endpoints at 3 months, worsening renal failure, and hypokalemia showed no significant differences between groups Conclusions: High loop diuretic doses are associated with poor outcomes in AHF patients, reflecting disease severity rather than harm from aggressive diuretic use. Furthermore, high diuretic doses do not seem to negatively affect kidney function.